The Continuous Strength Method for the design of stainless steel members under combined loading. Issue 2 (1st September 2021) - Arrayago, Itsaso; Real, Esther; Gardner, Leroy; Mirambell, Enrique
Abstract: The Continuous Strength Method (CSM) provides accurate cross‐section resistance predictions since allowance is made for the partial spread of plasticity and the beneficial effects of strain hardening. Although CSM design provisions for different loading conditions are available, the method was limited to the determination of cross‐sectional resistance until recent research by Arrayago et al. (2020) proposed a consistent new approach to the design of stainless steel hollow section members subjected to compression. Extension of the CSM to the design of stainless steel members subjected to combined compression and bending moment is presented in this paper. The analysis is based on numerical results generated in the current study and existing results collected from the literature on stainless steel hollow section members. The results demonstrate that the adoption of the CSM design equations to predict column strength considerably improves the accuracy of the calculated beam‐column capacities. The reliability of the proposed approach is demonstrated through statistical analyses performed in accordance with EN 1990.